Dvobarvni poskusi s kratkoživimi atomskimi stanji - Hrast, Mateja (Matrika, 2015)
The concept of a two-color experiment is presented through the example of dipole-forbidden excitation to doublyexcited helium states. To achieve those, we expose helium atoms to two simultaneous laser pulses, one from the ultraviolet and the other from the infrared region. This work presents two ways of simulating such an experiment: rate equations and the approach with density matrices, together with their limitations. In the end, the results of both simulations are presented, mentioning also the possibilities of the realization of the described experiment.
Keywords: atomic physics; atomska fizika; dvobarvni poskusi; helij; helium; two-color experiments